Emerging Molecular Drivers of Gene Expression Patterns in Roux-en-Y Gastric Bypass versus Vertical Sleeve Gastrectomy: Potential Implications for Cardiovascular Health - Maryam Mahjoubin-Tehran; Ali H. Eid; Tannaz Jamialahmadi; Bodor Bin Sheeha; Omar W. Althomali; Saheem Ahmad; Wael Almahmeed; Amirhossein Sahebkar (Bariatric Surgical Practice and Patient Care, 2026)
Objective: Vertical sleeve gastrectomy (VSG) and Roux-en-Y Gastric Bypass (RYGB) are common types of bariatric surgery. In this study, our aim was to identify differentially expressed genes in the duodenal tissue of Rattus norvegicus in a rat model after RYGB compared with VSG. Methods: We obtained the microarray profile of GSE169402 from the GEO database and identified differentially expressed genes by comparing the expression profiles of duodenal tissue genes after RYGB with those after VSG. Protein–protein interactions were analyzed using the STRING online tool. Results: Our analysis revealed that cluster 2, consisting of 20 nodes and 42 edges ( p -value < 1.0e-16), was the most significant cluster. The GO enrichment analysis demonstrated the roles of these genes in the GO Component of Lipid droplet. Moreover, KEGG analysis results discovered that the PPAR signaling pathway had the highest scores. We also explored the associations of these genes with diseases using DisGeNET. Our findings showed that ANGPTL4 , APOC2 , CIDEC , HMGCS2 , INSIG1 , PCK1 , PDK4 , PLIN2 , SERPINE1 , and SREBF1 , after RYGB were showed expression patterns overlapping with known CVD risk genes. On the other hand, upregulated genes such as Klf15 were found to inhibit lipogenesis. Conclusion: Overall, the present study suggests that RYGB is associated with differential expression of CVD-related genes in duodenal tissue, which may contribute to its superior cardiovascular outcomes compared with VSG. These hypothesis-generating findings from rat duodenal tissue require validation in human multitissue studies to confirm translational relevance to cardiovascular health outcomes.